2020
DOI: 10.1111/1755-0998.13158
|View full text |Cite
|
Sign up to set email alerts
|

High‐quality genome assembly and transcriptome of Ancherythroculter nigrocauda, an endemic Chinese cyprinid species

Abstract: Ancherythroculter nigrocauda is a cyprinid fish endemic of the upper reaches of the Yangtze River in China, where it is an important aquaculture and commercial species. It is also a threatened species as a result of overfishing, dam construction and water pollution. In this study, a chromosome-level genome assembly of A. nigrocauda is reported and built using PacBio sequencing and the Hi-C technology. The 1.04-Gb sequenced genome of A. nigrocauda contained 2,403 contigs, with an N50 length of 3.12 Mb. Then, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
(63 reference statements)
3
8
2
Order By: Relevance
“…After the Hi-C corrected contigs were placed in the ALLhic pipeline 14 for segmentation, orientation and sequencing, the final 99.49% of the assembled sequences were anchored to 24 pseudochromosomes with chromosome lengths that ranged from 31.72 Mb to 73.07 Mb (Table 3). This result is in agreement with the karyotype results which are based on cytological observations 15 , as many cyprinid fish such as Ctenopharyngodon idellus 16 , Ancherythroculter nigrocauda 17 , Hypophthalmichthys molitrix and Hypophthalmichthys nobilis 18 with chromosome numbers of 2n = 48. Further we manually curated the Hi-C scaffolding from the chromatin contact matrix in Juicebox (Fig.…”
Section: Methodssupporting
confidence: 92%
“…After the Hi-C corrected contigs were placed in the ALLhic pipeline 14 for segmentation, orientation and sequencing, the final 99.49% of the assembled sequences were anchored to 24 pseudochromosomes with chromosome lengths that ranged from 31.72 Mb to 73.07 Mb (Table 3). This result is in agreement with the karyotype results which are based on cytological observations 15 , as many cyprinid fish such as Ctenopharyngodon idellus 16 , Ancherythroculter nigrocauda 17 , Hypophthalmichthys molitrix and Hypophthalmichthys nobilis 18 with chromosome numbers of 2n = 48. Further we manually curated the Hi-C scaffolding from the chromatin contact matrix in Juicebox (Fig.…”
Section: Methodssupporting
confidence: 92%
“…The k‐mer analysis showed that the fall armyworm has high heterozygosity of 3.45% (Figure S1). An inflated assembly size relative to k‐mer based estimates has also been observed in other highly heterozygous species assemblies such as Ancherythroculter nigrocauda , Pyrocoelia pectoralis , and Oncopeltus fasciatus (Fu et al., 2017; Panfilio et al., 2019; Zhang et al., 2020). Previously released genomes indicated the genome size of the fall armyworm ranges from 358 Mb to 542 Mb (Table 1).…”
Section: Resultsmentioning
confidence: 74%
“…Nevertheless, the heterozygosity estimated for TARdn1 is one of the highest reported for a fish species. To our knowledge, this is the highest heterozygosity estimated for a fish through k -mer analysis, with other reported values ranging from 0.1% (Tibetan loach Triplophysa tibetana and Murray cod Maccullochella peelii ) to 0.9% (Java medaka Oryzias javanicus ) (Austin et al, 2017; Ge et al, 2019; Gong et al, 2018; Lu et al, 2020; Nguinkal et al, 2019; Takehana et al, 2020; Vij et al, 2016; Yang et al, 2019; H. H. Zhang et al, 2020; Zheng et al, 2021). Even the heterozygosity estimated through SNPs (0.64%) is high compared to estimations from other fish using the same method (e.g.…”
Section: Resultsmentioning
confidence: 63%